Evaluation of the efficacy of gingival crevicular blood in predicting the glycemic control - Mohammad Shereef; Namitha Xavier; Angel Fenol; Biju Balakrishnan; Lakshmi Puzhankara (Wolters Kluwer Medknow Publications, 2018)
Background and Aim: Diabetes has emerged as a major healthcare problem in India. Diabetes and periodontitis interact in a bidirectional manner; therefore, there is a need to screen patients for diabetes in dental clinics. Development of an intraoral blood sampling technique would make screening easier for dental practitioners. Routine oral examination of patients with periodontal inflammation with or without diabetes produce ample bleeding which can be used in glucometers for screening diabetes mellitus. Therefore, the aim is to assess if gingival crevicular blood (GCB) is as efficient as capillary finger prick technique in estimating the glycemic status. Settings and Design: This was a cross-sectional study. Materials and Methods: Fifty-eight participants with gingivitis or periodontitis with bleeding on probing from at least one site were chosen. Periodontal parameters such as Probing pocket depth and gingival index were measured using William's graduated periodontal probe. GCB and capillary finger prick blood (CFB) were collected for the estimation of blood glucose with the help of glucometer. Statistical Analysis: Performed using Pearson's correlation coefficient. Results: The Pearson correlation coefficient of GCB and CFB was 0.982 with a P < 0.001. Conclusion: It can be concluded that GCB can be used for the estimation of glycemic status.